2000
DOI: 10.1002/1098-2302(2000)37:4<253::aid-dev6>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The effects of medial preoptic area and amygdala lesions on maternal behavior in the juvenile rat

Abstract: The present study was designed to determine whether the medial preoptic area (MPOA) and the amygdala (AMYG) are involved in the expression of ``maternal'' behavior in juvenile rats as they are in the adult. Juveniles show many behaviors that are similar to the maternal behaviors shown by the postpartum female rat. Whether these behaviors are social in function, as opposed to parental, and hence mediated by different mechanisms from those regulating adult maternal behavior is not known. To test the roles of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
1
27
0
1
Order By: Relevance
“…As noted above, lesions of the amygdala do not produce consistent effects on nesting, although Oxley and Fleming (2000) have shown that lesions facilitate nest building in rats. This finding is consistent with the fact that MeA lesions facilitate other aspects of maternal care in rats, as well (Sheehan et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As noted above, lesions of the amygdala do not produce consistent effects on nesting, although Oxley and Fleming (2000) have shown that lesions facilitate nest building in rats. This finding is consistent with the fact that MeA lesions facilitate other aspects of maternal care in rats, as well (Sheehan et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…The most extensive data come from rats, in which the importance of the MPOA has been demonstrated through knife cuts lateral to the MPOA, and both electrolytic and cytotoxic lesions (Terkel et al, 1979; Jacobson et al, 1980; Miceli et al, 1983; Kalinichev et al, 2000; Oxley and Fleming, 2000; Olazabal et al, 2002). These manipulations virtually abolish nesting behavior and concomitantly impair other aspects of maternal behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to infant stimuli, infant cry and smiles activate the amygdala (Barrett et al, 2012; Seifritz et al, 2003; Swain et al, 2008), which has often been interpreted as a sign of emotional salience (Seifritz et al, 2003; Strathearn and Kim, 2013) or positive emotion associated with attachment (Leibenluft et al, 2004). On the other hand, in virgin rats, activation in the medial nucleus of the amygdala was associated with reduced maternal behaviors (Morgan et al, 1999; Oxley and Fleming, 2000). Thus, while increased activation of the amygdala to infant stimuli is interpreted as a more negative response to infants among typical adults (Riem et al, 2011), in mothers, it can be associated with more positive responses to one’s own infant (Barrett et al, 2012).…”
Section: Neurocognitive Mechanisms Underlying Parental Sensitivitymentioning
confidence: 99%
“…Other important regions are general motivational systems, such as the dopaminergic mesolimbic system, which includes the nucleus accumbens (NA), and areas implicated in selective attention and decision-making such as the medial prefrontal cortex (mPFC). 3,4 Specifically, several studies have shown that lesions in the mPOA or the vBNST, [5][6][7][8][9] as well as the impairment of the connectivity between the mPOA/vBNST and the mesolimbic dopaminergic system, [10][11][12] abolish the expression of maternal behaviour.…”
Section: Introductionmentioning
confidence: 99%